Mathematics

How do you find g(-3) if g(x) = x³ + 3x - 5?


Answers

Generic placeholder image

yassautumn

Reply

[latex]g(-3)=(-3)^3+3\cdot(-3)-5\\ g(-3)=-27-9-5\\ g(-3)=-41[/latex]

Generic placeholder image

TamaraTewksbury170

Reply

To resolve the matter of changing x into (- 3) ​​in equation : [latex]g(x) = x^{3} + 3x - 5[/latex] [latex]g(-3) = (-3)^{3} + 3(-3) - 5[/latex] [latex]g(-3) = -27 + (-9) - 5[/latex] [latex]g(-3) = -27 -9 - 5[/latex] [latex]\boxed{g(-3) = -41}[/latex]

Leave a Answer


Please use only default html tags.